The Karaites, a religious and linguistic minority in Eastern Galicia (Ukraine) 1772-1945 - Kizilov, M (2007)
﻿ The dissertation is dedicated to the history of the East European Karaite Jews (Karaites), a highly interesting ethno-religious Jewish group. It focuses on the Karaites of Galicia (Ukraine) from 1772 to 1945. The first four chapters of the dissertation are devoted to the Austrian period in the history of the Galician Karaites (1772-1918). Chapter One demonstrates that the Karaites represent an unparalleled example of preferential treatment of a Jewish community by the Austrian administration. Chapter Two provides readers with an overview of the "internal" history of the Karaite communities of Halicz and Kukizow. Chapter Three outlines the religious and ethnographic customs and traditions of the Galician Karaites. Chapter Four focuses on relations between the Karaites and their ethnic neighbours - the Slavs and the Ashkenazic Jews. Chapter Five is dedicated to the history of the Karaites in Polish Galicia between the two world wars. It is in this period that the Karaites started to become more and more separated from the Ashkenazic Jews. Chapter Six reconstructs the process of dejudaization and Turkicization of the Karaite community, highlighting the role of Seraja Szapszal, the Karaite ideological leader. It ends with an analysis of the history of the community during the period of the Nazi occupation. Chapter Seven outlines the ultimate decline of the Galician community after the Second World War. It also describes the current state of the Galician Karaite community and its historical legacy. The conclusion provides some essential remarks regarding the position of the Karaite case within the wider framework of Jewish and European history.